Scottish witchcraft eaudiobook A complete guide to authentic folklore, spells, and magickal tools. - Meiklejohn-Free, Barbara (Tantor Media, 2020)
Hear the Call of the Highlands for Powerful Magick, Healing, and Divination Take a journey through the magickal folk traditions of Scotland. Barbara Meiklejohn-Free, a Scottish hereditary witch, shares her own spiritual awakening into the craft and shows you how to integrate these practices into your own life. Discover the secrets of divination, scrying, faery magick, and communication with ancestors. Explore herb and plant lore and specific rituals to address what you most desire. Filled with inspiring anecdotes, craft history, and step-by-step instructions, this book will help you begin a new chapter of spiritual discovery.